Java cookbook. - Darwin, Ian F., ....- (Beijing : O'Reilly, 2001)
1.Getting started: compiling, running, and debugging 2.Interaction with the environment 3.Strings and things 4.Pattern matching with regular expressions 5.Numbers 6.Dates and times 7.Structuring data with Java 8.Object-oriented techniques 9.Input and output 10.Directory and filesystem operations 11.Programming serial and parallel ports 12.Graphics and sound 13.Graphical user interfaces 14.Internationalization and localization 15.Network clients 16.Server-side Java: sockets 17.Network clients II: applets and web clients 18.Web server Java: servlets and JSP 19.Java and electronic mail 20.Database access 21.XML 22.Distributed Java: RMI 23.Packages and packaging 24.Threaded Java 25.Introspection, or "a class named class" 26.Using Java with other languages
Keywords: Java (programmeertaal).; Programmatuurontwikkeling